The Influence of Transformational Leadership, Organizational Culture, and Incentives on The Performance of Permanent Employees at PT Bukit Makmur Mandiri Utama Jobsite Adaro Tutupan - Fernandes, Hendriko (Jurnal Indonesia Sosial Sains, 2025)
In dynamic industrial environments such as the mining support sector, employee performance is critical to achieving organizational goals. However, performance outcomes are often influenced by leadership quality, organizational culture, and reward systems, which are rarely examined collectively. This study aims to investigate the simultaneous and partial effects of transformational leadership, organizational culture, and incentives on the performance of permanent employees in the engineering division of PT Bukit Makmur Mandiri Utama, Adaro Tutupan jobsite. A quantitative approach was adopted using a survey distributed to 44 respondents, with data analyzed through path analysis using SmartPLS software. The results revealed that all three independent variables—transformational leadership, organizational culture, and incentives—positively and significantly influence employee performance, both partially and simultaneously. Among these, transformational leadership showed the strongest direct effect. These findings imply that strategic alignment of leadership behavior, a supportive organizational environment, and well-designed incentive systems are essential to optimizing employee productivity in project-based operational settings. The study offers actionable insights for HR development in the mining industry and serves as a reference for future research integrating psychological and contextual factors